Degradation modelling on temperature upon burst capacity of composite repaired pipeline - Thoo, Hui Sxin (2019)
Pipelines are the safest, efficient, and economic way for oil and gas transportation over a long distance. It is subjected to deterioration and damage, which can reduce their strength and structural integrity. Fiber-Reinforced Polymer (FRP) composites are used to repair defective steel pipes and it has been proven effective as it restored the loading capacity of steel pipe. However, FRP composites are susceptible to be degraded by several environmental factors such as temperature, moisture, ultraviolet radiation, thermal cycling, and mechanical fatigue. Degradation of FRP composites are expected to decrease the load bearing capacity of composite repaired steel pipe. Therefore, the purpose of this research is to study the effect of temperature towards the degradation of E-glass/Vinylester on composite repaired pipeline through finite element analysis (FEA). The E-glass/Vinylester composites were subjected to different temperatures which are 23°C, 60°C, and 95°C at 0-day, 360-days, 1080-days, and 1440-days. Ten finite element (FE) models were developed to simulate the effect of composite degradation upon the burst pressure of composite repaired pipeline. The results show that burst pressure of composite repaired steel pipe dropped significantly by 10.09% and 11.62% within 360-days at 60°C and 95°C, respectively. Meanwhile, a reduction of burst pressure by 7.29% at 1080-days was observed when the composite repaired pipe was subjected to 23°C. As a conclusion, degradation of E-glass/Vinylester composites over time has the effect on load bearing capacity of composite repaired steel pipe. Reduction of tensile strength in composite had reduced the burst capacity of composite repaired pipeline. This finding can be very useful in understanding the long-term durability of composite repaired steel pipe.